Governance, networks and leadership in a Mayan ecotourism cooperative in Yucatan, Mexico - Fernández-Aldecua, María José; García de Fuentes, Ana; Jouault, Samuel (Cooperativismo & Desarrollo, 2022)
The study applied a qualitative methodology to analyze an ecotourism mixed cooperative in Yucatan, Mexico, which contrary to the general and regional trend shows a greater quantitative and qualitative participation of women members. The objective is to identify the contingent factors that have been combined to promote female leadership and greater equity in gender relations between partners. Field techniques such as ethnography, semi-structured interviews and participant observation were used. Results indicate that a democratic governance, strong social networks, and a shared and inclusive female leadership are central elements for the construction of a community and an organizational and gender identity, supporting the survival and success of the social enterprise.
Keywords: indigenous cooperatives; transformational leadership; gender identity; ecotourism; governance